Why caring counts: Public value creation in smart specialisation through partnerships for regional innovation (PRI) - Riikka Poikela; Antti Mäenpää; Mika-Petri Laakkonen (European Journal of Spatial Development, 2023)
Smart specialisation is an instrument of the European Cohesion Policy and a key political principle to advance European competitiveness, innovation and welfare. Whereas smart specialisation is previously recognised for its focus on creating economic value through regional specialisation and new innovations, some recent arguments show that sustainable and social aspects are now defining the new smart specialisation strategy (McCann & Soete 2020; Pontikakis et al. 2022). In this paper, we examine the concept of public value to determine what a broader sustainable focus could mean for the next generation of smart specialisation strategies and how regions may use their entrepreneurial discovery processes (EDP) in a new way to combine vertical specialisation with more horizontal, sustainable and particularly social sustainability goals. Our inspection of public value via Moore’s strategic triangle and the smart specialisation literature indicate that the entrepreneurial discovery process can be viewed as a platform for conveying public value, which may also help in understanding how the entrepreneurial discovery process may become an open discovery process (ODP) in partnerships for regional innovation (PRO) implementation.